Electrospray application of guava seed oil for shelf life extension of guava fruit. (6th June 2022) - Kapoor, Swati; Gandhi, Neeraj; Kaur, Gurkirat; Khatkar, Sunil Kumar; Bala, Manju; Nikhanj, Pooja; Mahajan, BVC; Sharma, Deepansh
Summary: Guava seed oil (GSO) extracted from agro‐waste of the guava processing industry was used to prepare emulsion‐based edible coating. GSO ranging from 5% to 20% oil containing soy lecithin emulsifier was homogenised and ultrasonicated for preparation of stable emulsion. GSO majorly contained linoleic fatty acid and the mean particle size of GSO emulsions was in the range of 1.350–3.134 μm. Transmission electron microscopy showed uniform distribution of GSO particles in water, depicting the efficiency of soy lecithin as an effective emulsifier. Water‐based electrostatic spray gun was used as a spray mechanism, wherein the charged particles of GSO emulsion were sprayed onto fresh guava fruits. The electrospray coated and control fruits (without coating) were stored in lined corrugated fibreboard boxes at ambient conditions and analysed for physiological, physico‐chemical, colour and microbiological changes throughout the storage period. Guava fruits coated with 15% GSO showed the best results with respect to weight loss, firmness, spoilage and microbial load. Shelf‐life studies conclude that GSO‐coated fruits could be stored well till 10 days with better quality as compared to control fruits with only 6 days shelf life. Abstract : Graphical Abstract